(untitled) (International Journal of Language, Literacy and Translation, 2019)
This study primarily attempts at examining the mind style of the leading character in the 1997 film As Good as ItGets performed by Jack Nicholson as Melvin Udall, a novelist who is characterized as a misanthrope, and suffersfrom obsessive-compulsive disorder (OCD). The main aim of this paper is to examine the mind-modeling of thecharacter's mind for his unique odd mind style. This can be achieved by applying both qualitative and quantitativemethodologies. The adopted methodology is based basically on McIntyre and Archer (2010) and McIntyre (2015); itshares some of the perspectives that require using Wmatrix (Rayson, 2008) to perform the quantitative analysis inorder to validate the qualitative data. However, this study, does not aim to measure consistency. This paper aims at:first, verifying the usefulness of one of the corpus tools in understanding the deviant mind of the character. Second,analyzing key semantic domains of the speech of the main character as well as the keywords used by him. Inaddition to that, the researcher tries to benefit from cognitive linguistics schema theory in understanding the oddmind style of the character.